Anaplasma phagocytophilum infection modulates expression of megakaryocyte cell cycle genes through phosphatidylinositol-3-kinase signaling. - Supreet Khanal; Hameeda Sultana; John D Catravas; Jason A Carlyon; Girish Neelakanta (PLoS ONE)
Anaplasma phagocytophilum, the agent of human granulocytic anaplasmosis infects neutrophils and other cells from hematopoietic origin. Using human megakaryocytic cell line, MEG-01, we show that expression of cell cycle genes in these cells are altered upon A. phagocytophilum infection. Expression of several cell cycle genes in MEG-01 cells was significantly up regulated at early and then down regulated at later stages of A. phagocytophilum infection. Lactate dehydrogenase (LDH) assays revealed reduced cellular cytotoxicity in MEG-01 cells upon A. phagocytophilum infection. The levels of both PI3KCA (p110 alpha, catalytic subunit) and PI3KR1 (p85, regulatory subunit) of Class I PI3 kinases and phosphorylated protein kinase B (Akt/PKB) and inhibitory kappa B (IκB) were elevated at both early and late stages of A. phagocytophilum infection. Inhibition of PI3 kinases with LY294002 treatment resulted in significant reduction in the expression of tested cell cycle genes, A. phagocytophilum burden and phosphorylated Akt levels in these MEG-01 cells. Collectively, these results suggest a role for PI3K-Akt-NF-κB signaling pathway in the modulation of megakaryocyte cell cycle genes upon A. phagocytophilum infection.